EFFECT OF ADDING DRY YEAST AND FOLIC ACID ON IMPROVING THE PHYSIOLOGICAL AND PRODUCTIVE PERFORMANCE OF QUAIL. - Rasheed, Suha A.; Al Nuaimmi, S. M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the different effects of folic acid and/or saccharomyces cerevisiae on different aspects of Japanese quails. Eighty quail chicks were used, divided into four groups (20 chicks each), the first group was the control, treated with normal ration and drinking water. The second group was treated with saccharomyces cerevisiae 2.5% in the ration, the third group was treated with folic acid (5mg/L. in drinking water), whereas the last group was treated with both folic acid and yeast as stated above. All treatments were for seven weeks, then the birds were sacrificed, and blood was collected to undergo the parameters. Results revealed that the treatment with yeast or folic acid significantly (p<0.05) decreased both RBC and Hb while WBC elevated as a result of the treatment in both males and females. Bodyweight decreased as a result of treating quails with yeast and/or folic acid in both males and females. In males, the concentration of cholesterol and triglycerides reduced in all treatment groups compared to control, while in females, the cholesterol elevated in treatment groups, with no effect on triglycerides. Testosterone was elevated in males treated with folic acid and/ or yeast.